2018
DOI: 10.1111/epi.14477
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and treatment effects of cannabidiol in children and adults with treatment‐resistant epilepsies: Expanded access program results

Abstract: SummaryObjectiveSince 2014, cannabidiol (CBD) has been administered to patients with treatment‐resistant epilepsies (TREs) in an ongoing expanded‐access program (EAP). We report interim results on the safety and efficacy of CBD in EAP patients treated through December 2016.MethodsTwenty‐five US‐based EAP sites enrolling patients with TRE taking stable doses of antiepileptic drugs (AEDs) at baseline were included. During the 4‐week baseline period, parents/caregivers kept diaries of all countable seizure types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
144
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 12 publications
20
144
3
5
Order By: Relevance
“…In vitro studies and an in vivo generalized seizure model showed that cannabidiol reduced seizure severity, and in recent phase 3 trials, cannabidiol at doses up to 20 mg/kg/day was effective in reducing the frequency of treatment‐resistant seizures in patients with DS (where the target patient population included only pediatric patients) and LGS (where the target patient population included both pediatric and adult patients) . These data are supported by results published from a multisite open‐label expanded access program of cannabidiol, first in 214 pediatric and adult patients with treatment‐resistant epilepsies, and most recently in 607 patients …”
mentioning
confidence: 59%
“…In vitro studies and an in vivo generalized seizure model showed that cannabidiol reduced seizure severity, and in recent phase 3 trials, cannabidiol at doses up to 20 mg/kg/day was effective in reducing the frequency of treatment‐resistant seizures in patients with DS (where the target patient population included only pediatric patients) and LGS (where the target patient population included both pediatric and adult patients) . These data are supported by results published from a multisite open‐label expanded access program of cannabidiol, first in 214 pediatric and adult patients with treatment‐resistant epilepsies, and most recently in 607 patients …”
mentioning
confidence: 59%
“…Cannabidiol (CBD) is an unconventional compound which exerts antiepileptic properties through a novel multiple mechanism of action. In recent years, CBD has been used, in experimental way and at different dosages in children and adults, to treat several drug-resistant epilepsies, including LGS, with promising results in terms of long-term seizure frequency reduction and safety [85]. The efficacy and safety of CBD as add-on anticonvulsant therapy for patients with LGS has been assessed in two phase III placebo-controlled RCTs [86,87]; the former [86] involved 171 individuals with refractory seizures from 24 different clinical sites, who were randomly assigned to receive 20 mg/kg oral CBD daily or placebo during a 14-week treatment period.…”
Section: Cannabidiolmentioning
confidence: 99%
“…In 214 pediatric patients with childhood‐onset treatment‐resistant epilepsy (20% of whom had DS) treated with GW Pharmaceuticals' formulation of CBD in physician‐initiated expanded‐access programs, add‐on CBD reduced seizure frequency with an acceptable safety profile, with a second, recently completed analysis extending the findings through 96 weeks in 607 patients . A 14‐week, double‐blind, placebo‐controlled trial (GWPCARE1 Part B) in patients with DS demonstrated a significant reduction in convulsive seizure frequency with CBD vs placebo, with higher rates of adverse events (AEs; including somnolence and diarrhea) and reversible liver enzyme elevations …”
Section: Introductionmentioning
confidence: 99%